Towards Open Science Related Policies, Infrastructures and Practices - Tautkevičienė, Gintarė; Cesevičiūtė, Ieva (Qualitative and Quantitative Methods in Libraries, 2019)
Open Science has entered the global research area bringing about not only opportunities but also challenges that range from national to institutional in terms of policy-making, infrastructure development, academic culture and other issues. We need to embrace these challenges today to be able to use the opportunities of Open Science tomorrow. The aim of the paper is to survey the status quo of Open Science related policies, infrastructures and practices in HE institutions in Lithuania. The paper starts with a review of Open Science concept and initiatives. Then it addresses the recent Open Science related policy developments on the international level. The third part of the paper discusses the general preconditions for the implementation of Open Science, whereas the fourth part focuses on how these preconditions are manifested in Lithuania. Reference is made to the results of the survey on the research data management infrastructure that was carried out in April and repeated in November 2017 at the institutions of higher education in Lithuania. The survey consisted of questions on the policy documents and infrastructure for Open Access publications and data at the institutions of higher education. The results of this survey serve as a background for the account of Open Science related policies, infrastructures and practices at institutions of higher education in Lithuania.